Akad Murabahah pada Pembiayaan Modal Usaha dalam Perspektif Hukum Ekonomi Syariah - Hanifah, Mardalena; Pascadinianti, Meidana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 2 (2025), 2025)
Murabahah financing is structured as a sale–purchase agreement in which the financier discloses its acquisition cost and agreed profit margin to the purchaser. In practice at PT Permodalan Nasional Madani Mekaar Syariah, however, funding is disbursed as cash rather than via the delivery of specific goods, raising questions about the fulfillment of shariah-mandated sale conditions. This study examines the implementation of the murabahah contract in Mekaar Syariah’s business-capital financing through a sociological, descriptive approach. Primary data were collected via in-depth interviews with branch managers, officers, and clients; secondary data were drawn from organizational documents and DSN-MUI fatwas. Findings reveal that at the Kuantan Mudik branch, financing is provided in monetary form prior to any actual acquisition or transfer of goods, thereby failing to satisfy the essential sale elements prescribed by Islamic law and DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000. Although clients are formally authorized under a wakalah (agency) arrangement to purchase assets for their enterprises, many divert funds to non-productive, consumptive expenditures. The murabahah contract is executed only at disbursement, concurrently with a wakalah contract, without subsequent verification of goods procurement or ownership transfer.These practices contravene the fundamental requirements of murabahah, namely, the existence of a tangible asset, pre-contract negotiation of profit margin, and clear transfer of ownership. To align Mekaar Syariah’s operations with shariah principles, the institution must strengthen its operational protocols and internal controls, ensuring that financing transactions genuinely reflect a sale, purchase of specified goods